2021
DOI: 10.3390/jcs5090234
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of a Biocomposite Based on Carbon Nanotube and Graphene Nanoplatelet Reinforced Polymers: Analytical and Numerical Study

Abstract: Biocomposites based on thermoplastic polymers and natural fibers have recently been used in wind turbine blades, to replace non-biodegradable materials. In addition, carbon nanofillers, including carbon nanotubes (CNTs) and graphene nanoplatelets (GNPs), are being implemented to enhance the mechanical performance of composites. In this work, the Mori–Tanaka approach is used for homogenization of a polymer matrix reinforced by CNT and GNP nanofillers for the first homogenization, and then, for the second homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…A 3D mixer is ideal for the homogeneous mixing of powder; it may be more difficult with different bulk density, or proportions of mixing, or shape and particle size. The classical tumbling motion ensures that every particle of powder changes its position and mixes at every angle of motion, which reduce the clustering of materials with different densities on the outer periphery of the mixer, or at the center of the mixing mass [ 33 ]. The important parameters of a 3D mixture are rotor speed, mixing time, rotary direction, and filler loading.…”
Section: Specimen Preparation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…A 3D mixer is ideal for the homogeneous mixing of powder; it may be more difficult with different bulk density, or proportions of mixing, or shape and particle size. The classical tumbling motion ensures that every particle of powder changes its position and mixes at every angle of motion, which reduce the clustering of materials with different densities on the outer periphery of the mixer, or at the center of the mixing mass [ 33 ]. The important parameters of a 3D mixture are rotor speed, mixing time, rotary direction, and filler loading.…”
Section: Specimen Preparation Proceduresmentioning
confidence: 99%
“…The results showed that a clear improvement in the thermal stability of the composites increased with increasing MWCNTs content. Rouway et al [ 33 ] performed homogeneous mixing using the Mori–Tanaka approach for CNT and GNP nanofillers, and then the matrix was used with alfa and E-glass isotropic fibers. They investigated the elastic properties with the influence of the volume fraction Vf and the aspect ratio AR of the nanofiller.…”
Section: Introductionmentioning
confidence: 99%
“…These soft and hard nano materials have been applied on wall paintings, on paper and wood manufacts, [12][13][14][15] not only as consolidant but also as adjuvant in cleaning and antimicrobial treatments. Carbon based nanomaterials such as nanotubes, given their mechanical and elastic properties, 16 their capability to increase the resistance against UV radiation and their high hydrophobicity, have been used for example in the removal of the black crust from the surfaces of pentelic marbles from the Basilica Neptuni (Rome, Italy). 17 Even though many nanomaterials, both organic and inorganic, have been exploited in this field, giving promising results both in terms of consolidation and of cleaning treatments, to the best of our knowledge, the many features of nanodiamonds (ND) have not yet been exploited in the field of restoration of cultural heritage.…”
mentioning
confidence: 99%
“…[21][22][23] The addition of nanofillers is considered one of the most promising methods to enhance the mechanical properties of fibrous composites. In this regard, two routes have been used: (i) dispersion of nanofillers in the matrix 24,25,26 and (ii) growing or grafting of nanofillers onto the fiber surface. 27 Zaer-Miri et al 26 demonstrated that the 3 wt.% silanized-TiO 2 addition increased the ILSS of the jute fiber/epoxy composite by 43%.…”
Section: Introductionmentioning
confidence: 99%